2016
DOI: 10.1021/acsami.6b05901
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conducting Self-Assembled Metal–Organic Framework/Polyelectrolyte Hollow Hybrid Nanostructures

Abstract: Herein, a room temperature chemical process to synthesize functional, hollow nanostructures from zeolitic imidazolate framework-8 (ZIF-8) and poly(vinylphosphonic acid) (PVPA) is reported. Syntheses are initiated by physically blending the components-a process that is accompanied first by encapsulation of ZIF-8 crystallites by PVPA and then by fragmentation of the crystallites. The fragmentation process is driven by partial displacement of the methyl-imidazolate ligands of Zn(II) in ZIF-8 by phosphonate groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 45 publications
(106 reference statements)
0
47
0
Order By: Relevance
“…In a later study, these researchers reported on the room temperature synthesis of functional hollow nanostructures composed of poly(vinylphosphonic acid) (PVPA) and ZIF‐8 . For that, hollow hybrid nanostructures were fabricated by physical blending methods at room temperature, which possessed lower accessible surface areas that ZIF‐8 nanoparticles, due to the blocking of ZIF‐8 pores by the PVPA polymer.…”
Section: Mofs As Fillers In Mixed‐matrix Membranes For Pemfcmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later study, these researchers reported on the room temperature synthesis of functional hollow nanostructures composed of poly(vinylphosphonic acid) (PVPA) and ZIF‐8 . For that, hollow hybrid nanostructures were fabricated by physical blending methods at room temperature, which possessed lower accessible surface areas that ZIF‐8 nanoparticles, due to the blocking of ZIF‐8 pores by the PVPA polymer.…”
Section: Mofs As Fillers In Mixed‐matrix Membranes For Pemfcmentioning
confidence: 99%
“…A) Chemical structure of PVPA polymer. B) Plot of proton conductivity at different temperatures of PVPA@ZIF8 hollow nanostructures under anhydrous conditions …”
Section: Mofs As Fillers In Mixed‐matrix Membranes For Pemfcmentioning
confidence: 99%
“…Ceramic materials, as well as polymers, have been extensively studied for these applications. Furthermore, new types of materials including zeolites, solid acids, graphene oxide, carbon nanotubes, covalent organic frameworks, and metal organic frameworks (MOFs) have also demonstrated promising proton transport characteristics. Lately, a new porous bioinspired MOF (bioMOFs) design was reported to be a good proton conductor alternative as well .…”
Section: Introductionmentioning
confidence: 99%
“…These types of compounds display proton conductivities which increase with increasing temperature under anhydrous conditions, which may be the result of hydrogen bonding. A schematic representation is given in Figure . The reported results of Zn‐aminotriazolato‐oxalate and a sulfonated poly(phthalazinone ether sulfone ketone) compound showed enhanced proton conductivity and low permeability as compared to Nafion .…”
Section: Metal–organic Ligand Membranesmentioning
confidence: 99%
“…(b) Potential mechanism for proton transfer in zeolite imidazolate frameworks and PVPA hollow nanostructures. (Reprinted with the permission of ACS . )…”
Section: Metal–organic Ligand Membranesmentioning
confidence: 99%